The salakayan festival a celebration of Miagawanons bravery against the moro invasion of 1754. - Novilla, Alvin Joseph M
This is a study on the Salakayan Festival as an annual celebration of the Miagawanons' bravery against Moro invasion and its significance in their life, history and culture. It aims to provide the socio-historical context of the Salakayan Festival, to trace the origin and development of the celebration, to identify the factors that led the Miagawanons to commemorate the brave fight of its town folks against the Moro invasion of 1754, and to assess the significance of the event in the history and culture of Miagao., The research primarily employed interviews in gathering information. An interview guide was used and respondents included both the participants and the audience. The research also employed library and archival research, participatory observation and photo documentation. The Salakayan Festival as a socio-cultural celebration is focused on the re-enactment of the Moro invasion of Miagao in May 7, 1754. It depicts a singular act of courage of the town folks and manifests the desire of every Miagawanon to stand up and be counted in the battle to preserve the town's culture and environment. The Salakayan Festival plays an important role in the Miagawanons collective life. It draws the people closer. It provides a venue for the people to commemorate the brave struggle of the fellow Miagawanons' against the invading Moros. The Salakayan Festival started as a plain Moro-moro depicting the armed conflict between the Spaniards and Muslims. The celebration has been handed down to the present generation with changes and further improvements in order to adapt to the changing political and economic conditions. Despite the changes in the manner of celebration, the Salakayan Festival still embodies the conscious efforts of the Miagwanons to preserve their historical and cultural legacy.